The Stone Age plague: 1000 years of persistence in Eurasia - Andrades Valtueña, Aida; Stockhammer, Philipp (bioRxiv beta, 2016)
Molecular signatures of Yersinia pestis were recently identified in prehistoric Eurasian individuals, thus suggesting Y. pestis caused some form of disease in humans prior to the first historically documented pandemic. Here, we present six new Y. pestis genomes spanning from the European Late Neolithic to the Bronze Age (LNBA) dating from 4,800 to 3,700 BP. We show that all currently investigated LNBA strains form a single genetic clade in the Y. pestis phylogeny that appears to be extinct. Interpreting our data within the context of recent ancient human genomic evidence, which suggests an increase in human mobility during the LNBA, we propose a possible scenario for the spread of Y. pestis during the LNBA: Y. pestis may have entered Europe from Central Eurasia during an expansion of steppe people, persisted within Europe until the mid Bronze Age, and moved back towards Central Eurasia in parallel with subsequent human population movements.